Day trading attention : how to actually build brand and sales in the new social media world - Vaynerchuk, Gary (Harper Business, an imprint of HarperCollins Publishers, 2024)
"In his seventh business book, author, entrepreneur, and investor Gary Vaynerchuk offers advice to enhance brand development, grow sales, and beat the competition using modern advertising strategies grounded in social media"--